(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Afrianto WF, Hasanah LN, Metananda AA. 2023. Diversity of edible plants traded in the East Jakarta traditional markets, Indonesia. Biodiversitas 24: 6953-6968. Traditional markets provide limited assistance while facilitating transient or set-term direct retail interactions between buyers and sellers. Commodities traded in the traditional markets range from fresh produce, pantry, dairy, snacks, meat, fish, and wellness products. This study aimed to determine the ethnobotany of edible plant species in Indonesia’s East Jakarta traditional markets. This study used an ethnobotanical approach qualitatively. The data were collected using purposive sampling, which included 157 sellers. This study found that 140 edible plant species (181 landraces) in the East Jakarta traditional markets belong to 50 plant families. Most plants were fruits (102 species), with herbs as the most dominant life form (90 species). Most edible plants must be cooked before consumption (40%) as vegetables (68 species). In addition, 166 species are cultivated, 8 are semi-cultivated, and 7 are wild-type plants. The edible plants observed in the traditional markets in this study are classified as highly available (79%) and can be found in all seasons (91%). The East Jakarta traditional markets have an essential role as a place of economic botany that can help balance the economy and conservation efforts. Consequently, traditional markets recreate an essential social-cultural function by combining cultural and biological diversity on a small scale.